On the Effects of Ethical Climate(s) on Employees’ Behavior: A Social Identity Approach - Pagliaro, Stefano; Lo Presti, Alessandro; Barattucci, Massimiliano; Giannella, Valeria A.; Barreto, Manuela (Frontiers in Psychology, 2018)
The spread and publicity given to questionable practices in the corporate world during the last two decades has fostered an increasing interest about the importance of ethical work for organizations, practitioners, scholars and, last but not least, the wider public. Relying on the Social Identity Approach, we suggest that the effects of different ethical climates on employee behaviors are driven by affective identification with the organization and, in parallel, by cognitive moral (dis)engagement. We compared the effects of two particular ethical climates derived from the literature: An ethical organizational climate of self-interest, and an ethical organizational climate of friendship. Three hundred seventy-six workers completed measures of Ethical Climate, Organizational Identification, Moral Disengagement, Organizational Citizenship Behaviors, and Counterproductive Work Behaviors. Structural equation modelling confirmed that the two ethical climates considered were independently related to organizational identification and moral disengagement. These, in turn, mediated the effects of ethical climates on Organizational Citizenship Behaviors and Counterproductive Work Behaviors. We discuss results in light of the social identity approach, and present some practical implications of our findings.